Lifelong Physical Activity Prevents Aging-Associated Insulin Resistance in Human Skeletal Muscle Myotubes via Increased Glucose Transporter Expression - Bunprajun, Tipwadee (Public Library of Science, 2013)
Both aging and physical inactivity are associated with increased development of insulin resistance whereas physical activity has been shown to promote increased insulin sensitivity. Here we investigated the effects of physical activity level on aging-associated insulin resistance in myotubes derived from human skeletal muscle satellite cells. Satellite cells were obtained from young (22 yrs) normally active or middle-aged (56.6 yrs) individuals who were either lifelong sedentary or lifelong active. Both middle-aged sedentary and middle-aged active myotubes had increased p21 and myosin heavy chain protein expression. Interestingly MHCIIa was increased only in myotubes from middle-aged active individuals. Middle-aged sedentary cells had intact insulin-stimulated Akt phosphorylation however, the same cell showed ablated insulin-stimulated glucose uptake and GLUT4 translocation to the plasma membrane. On the other hand, middle-aged active cells retained both insulin-stimulated increases in glucose uptake and GLUT4 translocation to the plasma membrane. Middle-aged active cells also had significantly higher mRNA expression of GLUT1 and GLUT4 compared to middle-aged sedentary cells, and significantly higher GLUT4 protein. It is likely that physical activity induces a number of stable adaptations, including increased GLUT4 expression that are retained in cells ex vivo and protect, or delay the onset of middle-aged-associated insulin resistance. Additionally, a sedentary lifestyle has an impact on the metabolism of human myotubes during aging and may contribute to aging-associated insulin resistance through impaired GLUT4 localization.